Stability of stationary and periodic solutions equations in Banach space. (1997) - Dorogovtsev, A. Ya.
Abstract : Linear difference and differential equations with operator coefficients and random stationary (periodic) input are considered. Conditions are presented for the mean stability of stationary (periodic) solutions under small perturbation of the coefficients.